THE CONTRIBUTION OF HISTORICAL SOURCES IN THE BIOARQUEOLOGICAL AND CONTEXTUAL ANALYSIS OF FUNERAL PRACTICES DURING THE XIX CENTURY AT THE HISTORICAL MONUMENT OF SAN JOSÉ DEL MONTE DE LOS LULES (TUCUMÁN - ARGENTINA) - Taddei, Tamara Taddei (Centro de Estudios de Arqueología Histórica (CEAH) de la Universidad Nacional de Rosario, 2022)
This research is based on the revaluation of a human collection found in the San José del Monte de los Lules site (Tucumán, Argentina), which remained under the protection of the Institute of Archeology and Museum from 2001 to the present. The enhancement of it allowed, on the one hand, to assign the individuals to the republican period (XIX-XX century) and, on the other, to contribute knowledge about the social practices, health status and lifestyle of the people buried in the site. Likewise, the packaging conditions of the human remains under study were improved through the implementation of a preventive conservation protocol that advocates their ethical management, together with the generation of a protective context. To do this, we start from a triple approach that articulates bioarchaeological studies, funeral practices and historical analyzes. The analyzed sample is represented by five individuals, two of them of undetermined sex, two female individuals and one male, covering a wide age range (from infants to the elderly). They show signs of metabolic, infectious and functional diseases.